Fungsi dan Nilai Khayi (Perahu Perempuan) bagi Suku Sentani di Kampung Ayapo Kabupaten Jayapura - Windy Hapsari; Simon Abdi K. Frank; J. R. Mansoben (CENDERAWASIH: Jurnal Antropologi Papua, 2020)
This study discusses khayi, which focuses on how khayi function and value as a women's boat in the culture of the Sentani people. This research is ethnography with a qualitative approach and descriptive data analysis. Data collection techniques used were observation, interviews, recording and recording and literature study. Informants were selected based on purposive sampling. Then the data analysis used includes the process of data reduction, data display and data interpretation. The results showed Function of khayi is highly related to its shape. Khayi shape is an adaptive function of social culture life for Sentani tribe, especially in Ayapo village. Their knowledge of raw material and putting root of tree as the prow is an adaptive reaction to culture society. Its long, big shape has significant function to support and espouse fully activities of Sentani women. Value of khayi is an appreciative representation of Sentani men to their women for their significant roles in social culture cycle and family income and society as well.